The relationship between prospective memory and episodic future thinking in younger and older adulthood. Issue 2 (February 2016) - Terrett, Gill; Rose, Nathan. S.; Henry, Julie D.; Bailey, Phoebe E.; Altgassen, Mareike; Phillips, Louise H.; Kliegel, Matthias; Rendell, Peter G.
Episodic future thinking (EFT), the ability to project into the future to "preexperience" an event, and prospective memory (PM), remembering to perform an intended action, are both examples of future-oriented cognition. Recently it has been suggested that EFT might contribute to PM performance but to date few studies have examined the relationship between these two capacities. The aim of the present study was to investigate the nature and specificity of this relationship, as well as whether it varies with age. Participants were 125 younger and 125 older adults who completed measures of EFT and PM. Significant, positive correlations between EFT and PM were identified in both age groups. Furthermore, EFT ability accounted for significant unique variance in the young adults, suggesting that it may make a specific contribution to PM function. Within the older adult group, EFT did not uniquely contribute to PM, possibly indicating a reduced capacity to utilize EFT, or the use of compensatory strategies. This study is the first to provide systematic evidence for an association between variation in EFT and PM abilities in both younger and older adulthood and shows that the nature of this association varies as a function of age.